Obstacles to the Implementation of Active Learning Strategies in the Educational Process and Ways to Address Them from the Teachers' Perspective (A Field Study in Second-Cycle Basic Education Schools in Lattakia City) (Journal of Hama University, 2026)
The study aimed to identify the obstacles to implementing active learning strategies in the educational process and ways to address them from the perspective of second-cycle basic education teachers. The study sample consisted of (133) male and female teachers. To achieve the study objectives, the researcher used the descriptive-analytical approach, and adopted the questionnaire as a research and data collection tool. The questionnaire consisted of (24) paragraphs listed according to the five-point Likert scale, in addition to one open-ended question. Accordingly, the study results showed the following: Obstacles related to the educational environment are the most common and influential in implementing active learning strategies in the educational process, as the arithmetic mean for this dimension reached (4.03), which is a high score, while the arithmetic mean for the teacher-related obstacles dimension reached (3.86). Finally, comes the learner-related obstacles dimension, with an arithmetic mean of (3.75). The results showed statistically significant differences between the responses of second-cycle basic education teachers regarding the obstacles to implementing active learning strategies in the educational process according to the gender variable, in favor of females. The study results also showed no differences between them based on the variables of academic qualification and years of experience. In light of the study results, the researcher suggested the need to hold ongoing training courses and workshops to train teachers on applying active learning strategies; provide financial support to provide active learning tools and methods and facilitate their use; and prepare a teacher guide that includes mechanisms for implementing active learning strategies.